Avaliação do papel de receptores tipo Toll 2 e 4 na resposta imune de indivíduos sadios, reativos ou não ao teste tuberculínico, frente ao desafio in vitro com Mycobacterium tuberculosis - Covre, Luciana Polaco (2013)
It is believed that TST+ individuals represent a major reservoir of tuberculosis transmission, reason they can reactivate the latent TB bacilli and silently transmit Mycobacterium tuberculosis (Mtb) to other contacts. Related to active tuberculosis cases, the majority is caused by latent infection reactivation, thus the latency is still a major obstacle to achieving tuberculosis control. Toll-like receptors (TLR) particularly TLR2 and TLR4 can participate in the regulation of the immune system since they have the ability to drive the innate and adaptive immune response. In this study we aimed to evaluate the role of Toll-like receptors 2 and 4 in the immune response from tuberculin skin test positive (TST +) and tuberculin skin test negative (TST -) healthy individuals upon challenge in vitro with Mycobacterium tuberculosis. Twenty-four healthy volunteers were invited to participate in our study, 13 TST + and 11 TST - where were evaluated: 1) the frequency of regulatory T cells; 2) the microbicidal activity and 3) cytokines profile and nitric oxide production after Mtb infection with or without TLR2 and TLR4 blocking. TST + individuals showed higher frequency of regulatory T cells and bacterial load when compared to TSTgroup. TLR2 receptor blocking reduced the Tregs frequency and microbicidal capacity in the TST + individuals, different from observed in both TST + and TST - after TLR4 blocking, which showed an increased microbicidal activity and decreased IL10 production. Our data suggest that Mtb pre-exposure and / or environmental mycobacteria although lead to immunological memory in TST + individuals do not affect the ability of pathogen clearance. Moreover, we observed that TLR 2 and TLR4 receptors are capable of modulating the immune response against Mtb and may be targets for future anti-TB treatments and chemoprophylaxis of latent TB.